Increased arginase levels contribute to impaired perfusion after cardiopulmonary resuscitation. (October 2014) - Jung, Christian; Quitter, Felix; Lichtenauer, Michael; Fritzenwanger, Michael; Pfeil, Alexander; Shemyakin, Alexey; Franz, Marcus; Figulla, Hans R.; Pfeifer, Ruediger; Pernow, John
Abstract Objectives The postcardiac arrest syndrome occurs after global hypoxia leading to microcirculatory impairment. Nitric oxide (NO) is a key molecule regulating microvascular function. The enzyme arginase has been suggested to modulate microvascular function by regulating NO metabolism. Therefore, we investigated whether arginase increases following global hypoxia and resuscitation and tested whether arginase inhibition influences altered microcirculation in resuscitated patients. Methods To determine the effect of global hypoxia on circulating arginase levels, fourteen healthy subjects were exposed to hypoxia in a normobaric hypoxia chamber (FiO² = 9·9%). In addition, 31 resuscitated patients were characterized clinically, and arginase 1 was measured on days 1 and 3. In eight resuscitated patients, a microcirculatory analysis was performed using a sidestream darkfield microcirculation camera. Perfused capillary density (PCD) was recorded before and after sublingual incubation of N‐omega‐hydroxy‐nor‐l‐arginine (nor‐NOHA) alone or together with the NOS inhibitor NG‐monomethyl‐l‐arginine (l‐NMMA). Results Circulating arginase 1 levels increased in healthy volunteers following global hypoxia in the hypoxic chamber (P < 0·01). In addition, arginase 1 levels were higher on day 1 (69·1 ± 83·3 ng/mL) and on day 3 (44·2 ± 65·6 ng/mL) after resuscitation than in control subjects (P < 0·001). Incubation of the sublingual mucosa with nor‐NOHA increased microcirculatory perfusion (P < 0·001). This effect was inhibited by co‐incubation with K‐NMMA. Conclusions Circulating arginase 1 levels are increased following exposure to global hypoxia and in patients who have been successfully resuscitated after cardiac arrest. Topical arginase inhibition improves microcirculatory perfusion following resuscitation. This is of potential therapeutic importance for the postcardiac arrest syndrome.